2004
DOI: 10.1021/jm0498708
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Diarylacrylonitriles as a Novel Series of Small Molecule Sortase A Inhibitors

Abstract: On the basis of a hit from random screening, a novel class of small-molecule sortase A inhibitors was generated. The primary structure-activity relationship and the minimal structural requirements for potency were established through structural modifications and molecular modeling studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
103
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 23 publications
1
103
0
Order By: Relevance
“…Previous studies on small molecule inhibitors of sortases have been limited to the screening of 1000 compounds, which identified diarylacrylonitriles as potential inhibitors (18). In this study, compounds with IC 50 values between 10 and 1000 M were reported, and one compound functioned as competitive inhibitor with very favorable K i value (18).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies on small molecule inhibitors of sortases have been limited to the screening of 1000 compounds, which identified diarylacrylonitriles as potential inhibitors (18). In this study, compounds with IC 50 values between 10 and 1000 M were reported, and one compound functioned as competitive inhibitor with very favorable K i value (18).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, compounds with IC 50 values between 10 and 1000 M were reported, and one compound functioned as competitive inhibitor with very favorable K i value (18). Diarylacrylonitriles have been proposed to bind to the active site of sortase, although this hypothesis has not yet been supported by experimental evidence (18).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…inoculation of the pathogen (12,13). Earlier work used in vitro (inhibition of fluorogenic substrate cleavage) and virtual screening of compound libraries to identify sortase inhibitors (15,(52)(53)(54)(55)(56). Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies identified both competitive and noncompetitive inhibitors (57,58), isolated compounds have not yet been shown to inhibit in vivo sortase activity in staphylococci, i.e., the cleavage of sorting signals or the assembly of surface proteins into the bacterial cell wall (54,(59)(60)(61)(62). Many of the isolated compounds diminish or block staphylococcal growth, indicating that they cannot function as selective inhibitors of S. aureus sortase (53,61,63,64). Thus, the efficacy of sortase inhibitors as antiinfective therapeutics was heretofore not demonstrated (62,65).…”
Section: Discussionmentioning
confidence: 99%